Right ventricle to pulmonary artery coupling in patients undergoing transcatheter aortic valve implantation. Issue 2 (9th August 2018) - Sultan, Ibrahim; Cardounel, Arturo; Abdelkarim, Islam; Kilic, Arman; Althouse, Andrew D; Sharbaugh, Michael S; Gupta, Aman; Xu, Jeff; Fukui, Miho; Simon, Marc A; Schindler, John T; Lee, Joon S; et al.
Abstract : Objectives: To evaluate the prognostic value of the ratio between tricuspid annular plane systolic excursion (TAPSE)-pulmonary artery systolic pressure (PASP) as a determinant of right ventricular to pulmonary artery (RV-PA) coupling in patients undergoing transcatheter aortic valve replacement (TAVI). Background: RV function and pulmonary hypertension (PH) are both prognostically important in patients receiving TAVI. RV-PA coupling has been shown to be prognostic important in patients with heart failure but not previously evaluated in TAVI patients. Methods: Consecutive patients with severe aortic stenosis who received TAVI from July 2011 through January 2016 and with comprehensive baseline echocardiogram were included. All individual echocardiographic images and Doppler data were independently reviewed and blinded to the clinical information and outcomes. Cox models quantified the effect of TAPSE/PASP quartiles on subsequent all-cause mortality while adjusting for confounders. Results: A total of 457 patients were included with mean age of 82.8±7.2 years, left ventricular ejection fraction (LVEF) 54%±13%, PASP 44±17 mm Hg. TAPSE/PASP quartiles showed a dose-response relationship with survival. This remained significant (HR for lowest quartile vs highest quartile=2.21, 95% CI 1.07 to 4.57, p=0.03) after adjusting for age, atrial fibrillation, LVEF, stroke volume index, Society of Thoracic Surgeons Predicted Risk of Mortality. Conclusion: Baseline TAPSE/PASP ratio is associated with all-cause mortality in TAVI patients as it evaluates RV systolic performance at a given degree of afterload. Incorporation of right-side unit into the risk stratification may improve optimal selection of patients for TAVI.